2010
DOI: 10.1016/j.bpj.2010.05.038
|View full text |Cite
|
Sign up to set email alerts
|

NMR Structures of the Histidine-Rich Peptide LAH4 in Micellar Environments: Membrane Insertion, pH-Dependent Mode of Antimicrobial Action, and DNA Transfection

Abstract: The LAH4 family of histidine-rich peptides exhibits potent antimicrobial and DNA transfection activities, both of which require interactions with cellular membranes. The bilayer association of the peptides has been shown to be strongly pH-dependent, with in-planar alignments under acidic conditions and transmembrane orientations when the histidines are discharged. Therefore, we investigated the pH- and temperature-dependent conformations of LAH4 in DPC micellar solutions and in a TFE/PBS solvent mixture. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 61 publications
3
73
0
Order By: Relevance
“…1A). Circular dichroism studies have shown that, between these lysine residues, the central core of the peptide sequence, composed of alanine, leucine, and histidine residues, has a strong propensity to form an ␣-helical structure, 5 like the prototypic LAH4 peptide (30). To systematically investigate the molecular requirements for efficient transduction enhancement, Vectofusin-1 isomers were designed with different angles subtended by the two pairs of histidine residues (60°-180°) when represented as Schiffer-Edmundson wheels (Fig.…”
Section: Design and Evaluation Of Various Vectofusin-1 Isomers For Lementioning
confidence: 99%
“…1A). Circular dichroism studies have shown that, between these lysine residues, the central core of the peptide sequence, composed of alanine, leucine, and histidine residues, has a strong propensity to form an ␣-helical structure, 5 like the prototypic LAH4 peptide (30). To systematically investigate the molecular requirements for efficient transduction enhancement, Vectofusin-1 isomers were designed with different angles subtended by the two pairs of histidine residues (60°-180°) when represented as Schiffer-Edmundson wheels (Fig.…”
Section: Design and Evaluation Of Various Vectofusin-1 Isomers For Lementioning
confidence: 99%
“…lipid A in Gram-negative bacteria and lipoteichoic acid (Ozcan et al, 2006) in Gram-positive bacteria] on bacterial surfaces (Brogden, 2005;Mihajlovic & Lazaridis, 2010;Zhang et al, 2013). Although AMP amphiphilic sequences are highly diverse, the charge density of the cationic motif is predominantly provided by lysine or histidine residues (Park et al, 2003;Shanmugam et al, 2005;Mason et al, 2007;Georgescu et al, 2010;Khatami et al, 2014;Deslouches et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The N-and C-terminal lysines, two at each end, have been omitted for clarity. that these histidine-rich peptides exhibit a high degree of -helical conformations in micellar environments (Vogt & Bechinger, 1999;Georgescu & Bechinger, 2010). Remarkably, the outlines of the -helical structures are pH dependent and shift from a C-terminal (encompassing residues 9-24 at pH 4.1) to a more N-terminal position (residues 4-21 at pH 7.8).…”
Section: Membrane Topology Of Lah4 Peptidesmentioning
confidence: 97%
“…Two lysines at each terminus have been added to increase the solubility of the peptides in aqueous environments. The histidines exhibit pK a values around 6 and these residues can therefore be used to tune the hydrophobic moment of these sequences merely by changing the pH (Georgescu & Bechinger, 2010). The LAH4 peptides interact with membranes (Bechinger, 1996) and they exhibit antimicrobial activities (Vogt & Bechinger, 1999;Mason et al, 2009;Bechinger, 2011).…”
Section: The Lah4 Family Of Peptidesmentioning
confidence: 99%